ANALISIS KINERJA KEUANGAN DENGAN METODE ECONOMIC VALUE ADDED (EVA) PADA PT. FAST FOOD INDONESIA Tbk. - Fatichatur Rachmaniyah; Arief Yuswanto Nugroho (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2019)
This study aims to analyze the financial performance of PT. Fast Food Indonesia in 2013-2017 with the approach of Economic Value Added (EVA). This type of research is descriptive qualitative research with quantitative data types, because this study examines a case at PT. Fast Food Indonesia Tbk which is carried out intensively, deeply and comprehensively. The research analysis of financial performance of PT. Fast Food Indonesia, produces EVA> 0 (positive value), this can be said that the company has good financial performance. However, when viewed from the accumulation of calculation data from the 2013-2017 period, the EVA value fluctuated quite significantly and tended to decline, but it still could produce economic added value.